A Maltooligosaccharides Producing alpha-Amylase from Bacillus subtilis SDP1 Isolated from Rhizosphere of Acacia cyanophylla Lindley - OGAN, AYŞE; KAZAN, DİLEK (TAYLOR & FRANCIS INC, 2014)
Maltooligosaccharides producing amylases are required in the food industry, especially in breadmaking. The Bacillus subtilis strain SDP1 amylase hydrolyses starch to produce maltotriose and maltotetraose along with maltose after prolonged reactions of 5 h. Bacillus subtilis strain SDP1 was isolated from the rhizosphere of Acacia cyanophylla Lindley from the cukurova region of Turkey. The highest enzyme production was achieved with soluble starch as the carbon and yeast extract as the nitrogen source and at pH 7.0 and 37 degrees C. Under optimized culture conditions, 68.49 U/mL activity was obtained. SDP1 alpha-amylase had molecular weight of 61 kD. The optimum pH of the enzyme was 7.0 and was highly active at pH ranging from 5.0 to 9.0. The optimum temperature of the crude enzyme was 60 degrees C, and it retained 83% and 74% of its initial activity after 1 h and 2 h incubation periods, respectively, at 50 degrees C. While, Mn+2 has a stimulatory effect on the activity, Ca+2, Mg+2, Na+ did not effect the enzyme activity. Fe+3, Ni+2, Cu+2 and Co+2 had an inhibitory effect on SDP1 amylase activity.
Keywords: Bacillus subtilis; alpha-amylase; Acacia cyanophylla Lindley; maltotriose; maltooligosaccharide; MICROBIAL SOURCES; PURIFICATION; ALKALINE; OPTIMIZATION; HYDROLYSIS; SEQUENCE; CLONING; STRAIN; STARCH; CARBON